2019
DOI: 10.1002/jmri.26722
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sympathetic reinnervation after cardiac transplantation using hybrid cardiac PET/MRI: A pilot study

Abstract: Background Sympathetic reinnervation after heart transplantation (HTX) is a known phenomenon, which has an impact on patient heart rate variability and exercise capacity. The impact of reinnervation on myocardial structure has not been evaluated yet. Propose To evaluate the feasibility of simultaneous imaging of cardiac reinnervation and cardiac structure using a hybrid PET/MRI system. Study type Prospective / pilot study. Subjects Ten patients, 4–21 years after cardiac transplantation. Field Strength/Sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Heart rate variability has been evaluated in patients with NMS as a surrogate for reinnervation after cardioneuroablation (CNA). Pachon and colleagues [ 37 ] found that minimum and mean HR increased significantly at two years after CNA, but between the first and the second years, there were no essential changes, emphasizing the idea that no reinnervation occurred [ 38 ]. In addition, CNA eliminates the CI reflex and keeps most patients asymptomatic, maintaining exercise tolerance and also preventing pacemaker implantation [ 39 ].…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…Heart rate variability has been evaluated in patients with NMS as a surrogate for reinnervation after cardioneuroablation (CNA). Pachon and colleagues [ 37 ] found that minimum and mean HR increased significantly at two years after CNA, but between the first and the second years, there were no essential changes, emphasizing the idea that no reinnervation occurred [ 38 ]. In addition, CNA eliminates the CI reflex and keeps most patients asymptomatic, maintaining exercise tolerance and also preventing pacemaker implantation [ 39 ].…”
Section: Heart Rate Variabilitymentioning
confidence: 99%